THE USE OF CODE SWITCHING AMONG WAITER/WAITRESS IN RESTAURANT AT AMBER RESORT LOMBOK, INDONESIA - Abdul Hanan; Ainul Yakin; Endang Sri Wahyuni; Lalu Ahmad Zaki (JOEL: Journal of Educational and Language Research, 2024)
The aim of this research is analyzing the factors involved in the use of code-switching among waiter/waitress in Amber Beach Resort's restaurant operations. The data collection method used in this research is a documentation study based on various theoretical references obtained from various sources of books, scientific articles and print and online media, second is in-depth interviews with informants, informants in this study are waiters/waitress s at Amber Resort Lombok restaurant, Indonesia. The third is to conduct direct observation at the research location by observing the service process carried out by restaurant waiters at Amber Beach Resort Lombok and the use of language transfer while providing services to restaurant guests. Based on the results of the discussion above, it can be concluded that the researcher found four factors involved in code switching among waiter/waitress at the amber restaurant, the four factors are Participants (greeters - receivers), setting, topic, and function. The four factors are relevant to the theory that has been described previously with real activities at amber resort. It is indicated that the participants come from the same work area and the same situation, code-switching occurs at amber resort among waiters and managers with specific topics about restaurant and hotel management, and they use code-switching to say repetition and clarification, give and emphasis about something (to express solidarity), express tolerance to show the intention of clarifying the speech content for the interlocutor and to refine or strengthen requests or orders